Increased rates of Guillain-Barré syndrome associated with Zika virus outbreak in the Salvador metropolitan area, Brazil - Styczynski, Ashley R. (PLoS Negl Trop Dis, 2017)
In mid-2015, Salvador, Brazil, reported an outbreak of Guillain-Barré syndrome (GBS), coinciding with the introduction and spread of Zika virus (ZIKV). We found that GBS incidence during April–July 2015 among those ≥12 years of age was 5.6 cases/100,000 population/year and increased markedly with increasing age to 14.7 among those ≥60 years of age. We conducted interviews with 41 case-patients and 85 neighborhood controls and found no differences in demographics or exposures prior to GBS-symptom onset. A higher proportion of case-patients (83%) compared to controls (21%) reported an antecedent illness (OR 18.1, CI 6.9–47.5), most commonly characterized by rash, headache, fever, and myalgias, within a median of 8 days prior to GBS onset. Our investigation confirmed an outbreak of GBS, particularly in older adults, that was strongly associated with Zika-like illness and geo-temporally associated with ZIKV transmission, suggesting that ZIKV may result in severe neurologic complications.